Three Chinese pedigrees of A20 haploinsufficiency: clinical, cytokine and molecular characterization - Tian, Yi; Wu, Bingxuan; Peng, Linyi; Wang, Jian; Shen, Min (Frontiers in Immunology, 2022)
Objective: Haploinsufficiency of A20 (HA20) is a newly described rare autoinflammatory disease caused by TNFAIP3 gene mutations. HA20 has seldom been documented in the Chinese population. Herein, we report eight patients with HA20 from three unrelated families in China. Methods: Eight Chinese Han patients were diagnosed with HA20 in our department from 2018 to 2021. Their clinical data and genotypes were carefully documented and studied. The newly identified variants were functionally verified. We also conducted a systematic literature review of HA20, and the clinical characteristics and genotype of HA20 between the Chinese population and other populations were compared. Results: Eight HA20 patients from three families comprised six adults and two children. There was one man and seven women. The clinical characteristics included recurrent oral ulcers (8/8, 100%), fever (4/8, 50%), perianal ulcer (3/8, 38%), skin lesions (2/8, 25%), arthritis (1/8, 13%), and uveitis (1/8, 13%). Three TNFAIP3 variants, A547T, c.1906+2T>G, and R271X, were identified. Two novel variants, A547T and c.1906+2T>G, were validated to be pathogenic in our study. In a literature review a total of 126 patients with HA20 reported by 35 articles were included. The clinical phenotype of Chinese HA20 patients was similar to that of patients from other populations except for a lower frequency of genital ulcers (16.7% vs. 54.4%, p < 0.01). Autoantibodies were detectable in approximately one-third of the 126 patients, among which ANA and anti-thyroid antibodies were commonly seen. Conclusion: The rarity and diversity of phenotypes make the diagnosis of HA20 a huge challenge to physicians. HA20 should be considered in child-onset patients with manifestations that resemble Behçet’s syndrome, especially those whose family members have similar symptoms. Gene testing is critically helpful for the diagnosis of HA20. Two novel TNFAIP3 variants, A547T and c.1906+2T>G, were identified in this study.